On the Einthoven Triangle: A Critical Analysis of the Single Rotating Dipole Hypothesis - Gaetano D. Gargiulo; Paolo Bifulco; Mario Cesarelli; Alistair L. McEwan; Hossein Moeinzadeh; Aiden O’Loughlin; Ibrahim M. Shugman; Jonathan C. Tapson; Aravinda Thiagalingam (Sensors, 2018)
Since its inception, electrocardiography has been based on the simplifying hypothesis that cardinal limb leads form an equilateral triangle of which, at the center/centroid, the electrical equivalent of the cardiac activity rotates during the cardiac cycle. Therefore, it is thought that the three limbs (right arm, left arm, and left leg) which enclose the heart into a circuit, where each branch directly implies current circulation through the heart, can be averaged together to form a stationary reference (central terminal) for precordials/chest-leads. Our hypothesis is that cardinal limbs do not form a triangle for the majority of the duration of the cardiac cycle. As a corollary, the central point may not lie in the plane identified by the limb leads. Using a simple and efficient algorithm, we demonstrate that the portion of the cardiac cycle where the three limb leads form a triangle is, on average less, than 50%.